Միջազգային ռազմական համագործակցության հայեցակարգային հիմնադրույթների մասին - Գրիգորյան, Անդրանիկ (YSU Journal of International Affairs, 2014)
This article focuses on the theoretical aspects of the International Military Cooperation. As a result of analysis of official documents and theoretical literature we have tried to define a concept, and framework of its aims and activities. It is stated that though some defense diplomacy activities were part of interstate relations during the centuries, in the past two decades the framework of defense diplomacy has essentially been enlarged. Some changes, regarding the character of defense diplomacy, have also taken place. Special attention is paid to the problem of aims of International Military Cooperation of Armenia. Amongst them the following ones have central importance: creation of favorable conditions for the State Security, assistance to the reforms of defense sphere and the participation in the strengthening of International Security.
Keywords: International Military Cooperation, Defense Diplomacy, Military Diplomacy, Defense reforms, National and International Security, Defense Policy